2023
DOI: 10.1055/s-0043-1764196
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Transvaginal Prolapse Surgery on Anorectal Function

Abstract: Objective Pelvic floor dysfunction can manifest as a spectrum including anorectal dysfunction, vaginal prolapse, and urinary incontinence. Sacrospinous fixation is a procedure performed by gynecologists to treat vaginal prolapse. The present study aims to evaluate the impact of transvaginal prolapse surgery on anorectal function. Materials and Methods We conducted a retrospective review of patients undergoing sacrospinous fixation surgery for vaginal prolapse between 2014 to 2020. Those with anorecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
0
0
Order By: Relevance
“…Amongst those with faecal and urinary incontinence, there was a Perspective Chapter: Obstructed Defecation -From Diagnosis to Treatment DOI: http://dx.doi.org/10.5772/intechopen.1002688 statistically significant improvement in symptoms with this gynaecological surgery, illustrating the importance of these ligaments in anorectal and bladder function. A retrospective study also demonstrated an improvement in anorectal function with transvaginal surgery for vaginal prolapse (sacrospinous fixation), including a statistically significant improvement in the obstructed defaecation and constipation scoring system scores [21]. These studies support the concept of pelvic ligamentous integrity being an important element of normal anorectal function (Figure 1).…”
Section: Normal and Abnormal Defaecationmentioning
confidence: 65%
“…Amongst those with faecal and urinary incontinence, there was a Perspective Chapter: Obstructed Defecation -From Diagnosis to Treatment DOI: http://dx.doi.org/10.5772/intechopen.1002688 statistically significant improvement in symptoms with this gynaecological surgery, illustrating the importance of these ligaments in anorectal and bladder function. A retrospective study also demonstrated an improvement in anorectal function with transvaginal surgery for vaginal prolapse (sacrospinous fixation), including a statistically significant improvement in the obstructed defaecation and constipation scoring system scores [21]. These studies support the concept of pelvic ligamentous integrity being an important element of normal anorectal function (Figure 1).…”
Section: Normal and Abnormal Defaecationmentioning
confidence: 65%